Penerapan Pariwisata Berbasis Masyarakat Dalam Upaya Meningkatkan Industri Kreatif Di Kampung Lawas Maspati Kota Surabaya - Maftucha Maftucha; Imania Ayu Wulandari (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
As tourism develops in Indonesia, so is the rapidly growing tourist attraction offered by Indonesia. Not only natural tourism is offered to tourists, but the Government of Indonesia also creates an educational tourism that is by developing the potential of Tourism Villages and Tourist Villages that are quite interesting for the interest of tourists who want to visit somewhere. Maspati Laws Tourism Village is one of the leading tourism attractions in Surabaya. With this there are many developing creative industries created by the community. And this study aims to find out how the potential of Tourism in the community base in order to increase the Creative Business of the residents of Kampung Maspati and what positive impacts occur after the existence of a tourist area in the area. The development of the creative industry is progressing very rapidly and helps the economy of the surrounding community. And tourists who visit are on average to learn about how the management of the village that won the Green and Clean in Surabaya.Keywords: Existence, Creative Industry